Gender Digital Divide and Education in Latin America: A Literature Review - Ana Ancheta-Arrabal; Cristina Pulido-Montes; Víctor Carvajal-Mardones (MDPI AG, 2021)
Gender equity in education is one of the main targets for social justice and sustainable development. This literature review, from a gender approach, was conducted to understand how the gender digital divide (GDD) in information and communication technologies (ICT) and education are related in Latin American countries. A total of 28 articles have been analyzed as a satisfactory sample of the scientific literature to examine how this relation is explored and its influence, to acknowledge political stakeholders, as well as provide information and proposals to address the digital gender divide in education research in this region. The results show the need to develop research from the pedagogical and gender perspectives in Latin America, since they are not represented within an obvious problem.